Urinary tract infection following intradetrusor onabotulinumtoxina injection for non-neurogenic urgency incontinence: single- vs. multi-dose prophylactic antibiotic treatment regimens - Crouss, Tess; Kim, Youngwu; Lai, Erica; Chopra, Vini; Fagan, Matthew; Lipetskaia, Lioudmila (International Urogynecology Journal, 2023)
Introduction and hypothesis Urinary tract infection is one of the most common adverse events following onabotulinumtoxinA injection for urgency incontinence. Our hypothesis was that those undergoing injection for urgency incontinence who received more than one dose of prophylactic antibiotics have lower post-procedure urinary tract infection rates compared to those who receive a single dose. Methods We conducted a multi-center retrospective cohort study in females who underwent onabotulinumtoxinA injection for non-neurogenic urgency incontinence to evaluate the effect of single- vs. multi-dose prophylactic antibiotic regimens on the risk of post-procedure urinary tract infection. The primary outcome was the rate of urinary tract infection within 30 days of injection. Our sample size calculation required 136 subjects per group. Results Two hundred eighty-one patients were included from four centers. The single-dose cohort included 145 patients (51.6%), and the multi-dose cohort included 136 patients (48.4%). The mean age was 65 years, and patients were primarily Caucasian (81.4%). There was no difference in the rate of urinary tract infections diagnosed within 30 days of injection between the cohorts (single dose 13.8% vs. multi-dose 10.3%, p = 0.369). Those with a positive urine culture within 30 days of injection had a 15.2 times greater odds of having a post-procedure infection than those who did not (95% CI 3.19–72.53). There was no significant difference between the two cohorts in terms of adverse health events following injection. Conclusions In females with non-neurogenic urgency incontinence undergoing onabotulinumtoxinA injection, multi-dose prophylactic antibiotic regimens were not associated with lower post-procedure urinary tract infection rates.